Molecular-biological Methods of Research in Laboratory Diagnostics of Leprosy: Epidemiological Analysis, Genetic Determinants of Resistance to Antimicrobial Drugs - O. A. Obraztsova (State Scientific Center of Dermatovenereology and Cosmetology, 2018)
The review of literature presents analysis of the current state of molecular biological methods for research of Mycobacterium leprae. The characteristics and feasibility of application of the methods in use for diagnostics and epidemiological monitoring of the leprosy pathogen are discussed, as well as identification of possible genetic determinants of antibiotic resistance. The present knowledge is provided of genetic characteristics of mycobacteria of the above type, which enable to lay the foundations for development of methods for leprosy diagnostics, as well as also for their significant improvement.